Genotypic variability and inheritance of iron, phosphorus, potassium and zinc contents in segregating generations of peanut (Arachis hypogaea L.): GENOTYPIC VARIABILITY AND INHERITANCE OF P, K, Zn, Fe IN PEANUT - B C AJAY; H N MEENA; A L SINGH; M C DAGLA; NARENDRA KUMAR; S K BERA; A D MAKWANA; K A KALARIYA (Journal of Oilseeds Research, 2016)
Micronutrient malnutrition is a serious health issue affecting billions of people in developing countries. Peanut is rich in several mineral elements required for human nutrition. The objective of this study was to understand genetic variability and inheritance pattern of phosphorus (P), potash (K), zinc (Zn) and iron (Fe) concentrations in F2 and F3 generations of two peanut crosses namely Girnar-3 × FDRS-10 (Cross-A) and TG-37A × FDRS-10 (Cross-B). Pshell, Znshell, Kshell, Feshell, and Fekernel were positively skewed indicating additive gene action. Kurtosis formost of the characters moved in positive direction from F2 to F3 generation indicating a reduction in variation as generation advances.Phenotypic coefficient of variance (PCV) and genotypic coefficient of variance (GCV) revealed that traits were under genetic control and possessed substantial variability and hence a good scope for improving these characters. Both additive and non-additive types of gene actions were observed with the predominance of additive gene action for the inheritance of P, K, Fe and Zn in shell and kernels. Dominance variance (H) also played an important role in the inheritance of P, K, Fe and Zn in peanut. Average degree of dominance for most of the traits was greaterthan unityindicating over dominance forthese traits. Mineral elements had significant association among themselves but very few associations with pod yield. Selection and hybridization followed by pedigree breeding method are suggested in the later generations for genetic improvement to identify high yielding peanut genotypes rich in P, K, Fe and Zn.